Intensified equipment for producing high purity mtbe - Mohamad Rizza, Othman; Zulkifly, Jemaat; Chin, Sim Yee; Mohd Arman, Abd Kadir; Hairul Hisham, Ismail; Shafie, Mohammad; Faried, Abdullah (2021)
MTBE is produced from reaction between isobutene and methanol . HP MTBE is obtained from purification of industrial grade MTBE to purity of ≥ 99.7 wt% . HP MTBE is used in agriculture, pharmaceutical, cosmetics, food and chemical intermediates. Industrial grade MTBE contain contaminants i.e., isobutene, tertiary butanol, methanol, methyl sec-butyl ether or water. Analysis of 11 components in IG MTBE founds 41 azeotropes. 7 related to MTBE. Few options to break azeotrope i.e., pressure swing distillation, extractive distillation, membrane etc. These approaches are however complex.